Teleservice to the population of Rio Grande do Norte during the COVID-19 pandemic (Research, Society and Development, 2020)
Due to the magnitude of the new coronavirus pandemic, the routine of the general population and health services were modified in recent months. Much of the service to the population has started to be done mainly at a distance, with the help of technology tools, for instance, phones and computers, avoiding possible exposures to the virus. The aim of this study was to characterize the activities carried out in a university extension project developed by the Federal University of Rio Grande do Norte. This is a descriptive, observational, qualitative and quantitative study. The teleservice operated through a call-center, from the website Orienta Coronavirus RN and WhatsApp. The work was carried out by students, teachers and health professionals from some institutions, all qualified to offer reliable information to society. In total, 2,041 attendances were made to the population of the state of Rio Grande do Norte, which 1,075 occurred through the call center, 710 through whatsapp and 256 through the Orienta Coronavirus RN website. Therefore, the project collaborated in reducing the population uncertainties about COVID-19, decreasing the search for information in the health system, as well as contributing to the academic training of students from the interprofessional perspective.